Vom Werdegang eines Soziologen zum Staatspräsidenten: Fernando Henrique Cardoso - Müller-Plantenberg, Urs (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1995)
F. H. Cardoso was one of the leading Latin American sociologists in the 60s and 70s and was a founder of the "Theory of Dependency" (as it was later called byothers). In the 80s he went into politics, became a Senator and Minister. 1994 he was elected the Brazilian President of the State as the socialdemocratic candidate with help from the right.